Epicardial‐derived adrenomedullin drives cardiac hyperplasia during embryogenesis. Issue 2 (7th November 2013) - Wetzel‐Strong, Sarah E.; Li, Manyu; Klein, Klara R.; Nishikimi, Toshio; Caron, Kathleen M.
<x xml:space="preserve">Abstract</x> Background: Growth promoting signals from the epicardium are essential for driving myocardial proliferation during embryogenesis. In adults, these signals become reactivated following injury and promote angiogenesis and myocardial repair. Therefore, identification of such paracrine factors could lead to novel therapeutic strategies. The multi‐functional peptide adrenomedullin (Adm = gene, AM = protein) is required for normal heart development. Moreover, elevated plasma AM following myocardial infarction offers beneficial cardioprotection and serves as a powerful diagnostic and prognostic indication of disease severity. Results: Here, we developed a new model of Adm overexpression by stabilizing the Adm mRNA through gene‐targeted replacement of the endogenous 3′ untranslated region. As expected, Admhi/hi mice express three‐times more AM than controls in multiple tissues, including the heart. Despite normal blood pressures, Admhi/hi mice unexpectedly showed significantly enlarged hearts due to increased cardiac hyperplasia during development. The targeting vector was designed to allow for reversion to wild‐type levels by means of Cre‐mediated modification. Using this approach, we demonstrate that AM derived from the epicardium, but not the myocardium or cardiac fibroblast, is responsible for driving cardiomyocyte hyperplasia. Conclusions: AM is produced by the epicardium and drives myocyte proliferation during development, thus representing a novel and clinically relevant factor potentially related to mechanisms of cardiac repair after injury. Developmental Dynamics 243:243–256, 2014. © 2013 Wiley Periodicals, Inc.